PENGUKURAN TINGKAT RADIOAKTIVITAS 210Pb DAN 40K PADA TEMBAKAU ROKOK SERTA ESTIMASI DOSIS EFEKTIF YANG DITERIMA DARI MEROKOK - Achmad Chalid Afif; Eko Hidayanto; Zaenal Arifin; Poppy Intan Tjahaja; Putu Sukmabuana (Youngster Physics Journal, 2014)
The radioactivity in tobacco leaves assessment collected from 14 popular brand in Indonesia. Cigarette was studied in order to find activity concentration of 210Pb and 40K in a cigarette sample, and the effective dose induced to smokers from cigarette tobacco due to the naturally occurring radionuclides, such as 210Pb and 40K. It was concluded that the activity consentration of radioisotope 210Pb varied from 2,22 Bq/kgto 5,56 Bq/kg with average 3,968 ± 1.042 Bq/kg, 210Pb originated from the air and was deposited onto the tobacco leaves and trapped by trichomes, while for 40K from 8,89 Bq/kgto 15,56Bq/kg with average11,75 ± 1,782 Bq/kg.40K in the tobacco leaves was due to root uptake either from soil or fertilizer. The annual effective dose do to inhalation for adults smokers for 210Pb from 16,47 µSv/year to 41,18 µSv/year with average 29,42 ± 7,772 µSv/year. This dose must be compared with the average worldwide exposure to natural radiation source 2,4 mSv/year and especially the part due to inhalation which is 1,26 mSv/year.Keywords: Radioactivity, tobacco leaves, effective dose, smoking